Antiviral and quality effects of chemical elictors and Cucumber Mosaic Virus (CMV) infection on tomato plants and fruits - Kalogirou, Maria (Cranfield University, 2012)
Cucumber mosaic virus (CMV) has emerged as one of the most serious threats to tomato cultivation in Greece. In the present study the effects of Benzothiadiazoles (BTH) and pyraclostrobin against mechanically or aphid-transmitted CMV in tomato plants, of hybrid F1 Clodin, were investigated in greenhouse experiments. BTH was confirmed as capable of inducing systemic acquired resistance (SAR) in tomato seedlings against CMV, while pyraclostrobin was not. Responses to BTH application and/or CMV inoculation on Spanish tomato hybrid Delos (BTH, BTH+CMV, CMV treatments) were monitored during winter and spring season in Greece. In both seasons the SAR derived from BTH application suppressed CMV. BTH treatment presented increased plant growth, fruit size and marketable tomato yield compared to CMV and BTH+CMV treatments, whereas decreased compared to healthy control. CMV treatment caused the most severe stunting of tomato plants among the examined treatments and resulted in yield loss of marketable fruits, although the total fruit number was higher versus to other treatments. Cont/d.